PENGARUH MODEL SNOWBALL THROWING TERHADAP HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN PKn DI SD INPRES XX SOLOT - Bera, Lukas (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2020)
ABSTRACT This study aims to determine student learning outcomes by using the snowball throwing model on PKn subjects in the diversity of ethnic groups in Indonesia towards the learning outcomes of students in class V SD Inpres XX Solot Nita District, Sikka Regency. This research is a quantitative study with the tipe of experimental research method used in this study using the pre-experimental (nondesings) type one-group pretest-design method. The population and research sample were all students of class V which numbered 14 students. The test instrument used to determine is in the form of a pre-test and post-test. Based on the learning outcomes the values obtained the average experimental class in the group that was treated before that is 67,5 (pre-test) and the group that has been treated 8,21 (post-test) from the results of hypothesis testing and the basis of taking the value is significant. (2-tailed) is 0,000 while the significance level is 0,05. Eating a probability value of 0,05 or 0,000 is smaller than 0,05. This means H is accepted and H0 is rejected. Thus the influence of the application of the snowball throwing model on the PKn learning outcomes in the material of Ethic Diversity in Indonesia is the Class V Elementary School Student Inpres XX Solot Sikka District. Sikka Regency 2018/2019. Keywords: the application of the snowball throwing model, learning outcomes.